Technical and radiological image quality comparison of different liquid crystal displays for radiology - Dams FE (Dove Medical Press, 2014)
Francina EM Dams,2 KY Esther Leung,1 Pieter HM van der Valk,2 Marc CJM Kock,2 Jeroen Bosman,1 Sjoerd P Niehof1 1Medical Physics and Technology, 2Department of Radiology, Albert Schweitzer Hospital, Dordrecht, The Netherlands Background: To inform cost-effective decisions in purchasing new medical liquid crystal displays, we compared the image quality in displays made by three manufacturers. Methods: We recruited 19 radiologists and residents to compare the image quality of four liquid crystal displays, including 3-megapixel Barco®, Eizo®, and NEC® displays and a 6-megapixel Barco display. The evaluators were blinded to the manufacturers' names. Technical assessments were based on acceptance criteria and test patterns proposed by the American Association of Physicists in Medicine. Radiological assessments were performed on images from the American Association of Physicists in Medicine Task Group 18. They included X-ray images of the thorax, knee, and breast, a computed tomographic image of the thorax, and a magnetic resonance image of the brain. Image quality was scored on an analog scale (range 0–10). Statistical analysis was performed with repeated-measures analysis of variance. Results: The Barco 3-megapixel display passed all acceptance criteria. The Eizo and NEC displays passed the acceptance criteria, except for the darkest pixel value in the grayscale display function. The Barco 6-megapixel display failed criteria for the maximum luminance response and the veiling glare. Mean radiological assessment scores were 7.8±1.1 (Barco 3-megapixel), 7.8±1.2 (Eizo), 8.1±1.0 (NEC), and 8.1±1.0 (Barco 6-megapixel). No significant differences were found between displays. Conclusion: According to the tested criteria, all the displays had comparable image quality; however, there was a three-fold difference in price between the most and least expensive displays. Keywords: data display, humans, radiographic image enhancement, user-computer interface, liquid crystals